Upaya Guru Dalam Mengatasi Speech Delay Pada Anak Usia 5–6 Tahun Di Tk Yasalmuna Palangka Raya - Rina Yayang Sari; muzakki muzakki; Aghnaita Aghnaita (Prodi Pendidikan Islam Anak Usia Dini Sekolah Tinggi Agama Islam Negeri Mandailing Natal- Sumatera Utara, 2026)
Language is an essential aspect of early childhood development because it functions as a means of communication in daily life. However, not all children develop language skills according to their developmental stages. One of the language development disorders experienced by children is speech delay. This study aims to identify the characteristics of children with speech delay and the teachers’ efforts to overcome speech delay in children aged 5–6 years at TK Yasalmuna Palangka Raya. This research employed a descriptive qualitative approach with a field research design. Data were collected through observation, interviews, and documentation. The research subjects consisted of B1 and B2 classroom teachers, the principal, and two children experiencing speech delay. The results showed that children with speech delay demonstrated minimal verbal responses, limited vocabulary, unclear pronunciation, and difficulty forming simple sentences. Teachers’ efforts to overcome speech delay included singing activities, simple question-and-answer sessions, storytelling using pictures, picture guessing games, and positive reinforcement. After receiving gradual stimulation, the children showed improvement in speaking confidence, vocabulary development, and verbal responses during classroom activities.